2014
DOI: 10.1128/cvi.00179-14
|View full text |Cite
|
Sign up to set email alerts
|

Production and Preclinical Evaluation of Plasmodium falciparum MSP-1 19 and MSP-3 11 Chimeric Protein, PfMSP-Fu 24

Abstract: A Plasmodium falciparum chimeric protein, PfMSP-Fu 24 , was constructed by genetically coupling immunodominant, conserved regions of two merozoite surface proteins, the 19-kDa region C-terminal region of merozoite surface protein 1 (PfMSP-1 19 ) and an 11-kDa conserved region of merozoite surface protein 3 (PfMSP-3 11 ), to augment the immunogenicity potential of these blood-stage malaria vaccine candidates. Here we describe an improved, efficient, and scalable process to produce high-quality PfMSP-Fu 24 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…There is high level of interest in developing adjuvants that can stimulate potent CD8 and CD4 T cell responses to subunit antigens. Carbomer (acrylic acid polymers)-based adjuvants (CBA) are components of several veterinary vaccines, and known to safely elicit potent neutralizing antibodies to malarial and HIV envelope glycoproteins in mice and nonhuman primates (Menon et al, 2015, Gupta et al, 2014, Anlar et al, 1993. We have also reported that the carbomer-based nano-emulsion adjuvant, Adjuplex (ADJ; Advanced Bioadjuvants), elicits tissue-resident memory CD8 T cells in the lungs, and protects against influenza A virus in mice (Gasper et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is high level of interest in developing adjuvants that can stimulate potent CD8 and CD4 T cell responses to subunit antigens. Carbomer (acrylic acid polymers)-based adjuvants (CBA) are components of several veterinary vaccines, and known to safely elicit potent neutralizing antibodies to malarial and HIV envelope glycoproteins in mice and nonhuman primates (Menon et al, 2015, Gupta et al, 2014, Anlar et al, 1993. We have also reported that the carbomer-based nano-emulsion adjuvant, Adjuplex (ADJ; Advanced Bioadjuvants), elicits tissue-resident memory CD8 T cells in the lungs, and protects against influenza A virus in mice (Gasper et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, lack of such an antigenic competition has been reported earlier for other malaria fusion proteins [23,24,27,33]. These results highlight the potential of the approach of using fusion chimeras comprised of key antigenic determinants of different antigens for subunit vaccine development.…”
Section: Resultsmentioning
confidence: 63%
“…First, the protein was expressed and purified with ease in relatively higher yields than its individual components; PfMSP-3 11 was purified from inclusion bodies and yields of soluble PfMSP-1 19 were low [27,33]. Second, the conformational integrity of PfMSP-1 19 fragment was maintained which is essential for producing invasion inhibitory antibodies to this fragment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations